Sero-prevalence surveillance to predict vaccine-preventable disease outbreaks; a lesson from the 2014 measles epidemic in Northern Vietnam - Choisy, M; Trinh, S; Nguyen, T; Nguyen, T; Mai, Q; Pham, Q; Tran, N; Dang, D; Horby, P; Boni, M; Bryant, J; Lewycka, S; et al. (Oxford University Press, 2019)
Background: During the first half of 2014, a severe outbreak of measles occurred in northern Vietnam, causing 15 033 confirmed cases and 146 deaths. Methods: To evaluate the population-level seroprevalence of protection against measles in the period before the outbreak, we made use of an existing age-stratified serum bank, collected over the year before the outbreak, between November 2012 and December 2013, from 4 sites across the country (Hanoi, Hue, Dak Lak, and Ho Chi Minh City). Data from the UNICEF’s Multiple Indicator Clustered Surveys (MICS), carried out in Vietnam during the first quarter of 2014, were used to assess the vaccine coverage in 6 ecological regions of Vietnam. Results: Results revealed a large discrepancy between levels of protection, as estimated from the serology and vaccine coverage estimated by UNICEF’s MICS. Variation in seroprevalence across locations and age groups corresponded with reported numbers of measles cases, most of which were among the 0–2-year-old age group and in the northern part of the country. Conclusions: Our study presents a strong case in favor of a serosurveillance sentinel network that could be used to proactively tune vaccination policies and other public health interventions.